2009
DOI: 10.2466/pms.109.2.500-516
|View full text |Cite
|
Sign up to set email alerts
|

Preparatory EMG Activity Reveals a Rapid Adaptation Pattern in Humans Performing Landing Movements in Blindfolded Condition

Abstract: The main questions addressed in this work were whether and how adaptation to suppression of visual information occurs in a free-fall paradigm, and the extent to which vision availability influences the control of landing movements. The prelanding modulation of EMG timing and amplitude of four lower-limb muscles was investigated. Participants performed six consecutive drop-landings from four different heights in two experimental conditions: with and without vision. Experimental design precluded participants fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 23 publications
6
27
0
Order By: Relevance
“…There were no significant differences in the sagittal-plane kinematics between the looking-up and looking-down conditions, which support previous studies examining the effect of vision on feed-forward motor control (Magalhães & Goroso, 2009). Magalhães and Goroso (2009) found that participants exhibited similar muscle activation patterns in the no-vision condition to that observed when performing the jump-landing task with vision available.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…There were no significant differences in the sagittal-plane kinematics between the looking-up and looking-down conditions, which support previous studies examining the effect of vision on feed-forward motor control (Magalhães & Goroso, 2009). Magalhães and Goroso (2009) found that participants exhibited similar muscle activation patterns in the no-vision condition to that observed when performing the jump-landing task with vision available.…”
Section: Discussionsupporting
confidence: 89%
“…There were no significant differences in the sagittal-plane kinematics between the looking-up and looking-down conditions, which support previous studies examining the effect of vision on feed-forward motor control (Magalhães & Goroso, 2009). Magalhães and Goroso (2009) found that participants exhibited similar muscle activation patterns in the no-vision condition to that observed when performing the jump-landing task with vision available. The authors suggested the central nervous system rapidly adapted the lack of visual information through other afferent sources and feed-forward control, such as learned responses and previous experience with tasks (Magalhães & Goroso, 2009).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Two studies of myofeedback showed positive results after 4 weeks training (Hermens and Hutten 2002; Voerman et al 2007). One study further supported the rapid changes in individual’s motor program after being provided visual information (EMG) (Magalhães and Goroso 2009). The significant increase in working activity in the muscular strength training group and among controls was not found in this group.…”
Section: Discussionmentioning
confidence: 84%